Nonsurgical neovagina creation in congenital vaginal agenesis: a case report of movement-based dilator therapy - Katherine Miles, P.T., D.P.T., W.C.S; Shana Miles, M.D., Ph.D (Elsevier, 2023)
Objective: To report the use of progressive, high-frequency movement-based dilator therapy (MBDT) to create a neovagina in a patient with congenital vaginal agenesis. Design: Case report. Setting: Tertiary care military hospital. Patient(s): A 22-year-old woman with congenital vaginal agenesis. Intervention(s): Self-directed MBDT. Main Outcome Measure(s): Vaginal elongation by self-directed MBDT. Result(s): The patient achieved a 6.5-cm vaginal length after 6 pelvic health physical therapy sessions over a span of 4 months of progressive, high-frequency MBDT. Conclusion(s): Progressive, high-frequency MBDT should be considered as part of a first-line dilator therapy regimen for patients with congenital vaginal agenesis interested in creating a neovagina.